Governança e nivel de maturidade a adesão de boas praticas: um estudo em cooperativas de crédito - Ribeiro Junior, Roberto Marchelli (2016)
The adoption of good corporate governance practices in credit union is essential, so that the Brazilian Central Bank demands its adoption and edited, in 2016, the Resolution 4.454, that attributed to the external audits the verification of the implantation. The Credit Unions is the segment that presents large-scale indicators of growing and, although its participation is still modest in the National Financial System, it is fundamental for the Brazilian`s economy. It is the segment that takes action in the rates and costs reduction to citizens, encourages the credit and the financial education and it is the third largest network service of the country, going to places that no bank is. Because of the these facts and of the researcher´s ten years of experience acting in the segment of credit unions – consultancy, accountancy management, cooperativist administration, this dissertation was developed with the aim of investigating if the cooperatives of credit classical of free admission of members located in the state of Minas Gerais and affiliated to Central Sicoob Cecremge embrace good governance corporative practices recommended by the Brazilian Central Bank and in which level of maturity they are. The present work has carried out a tool that allows the credit unions to be aware of their levels of maturity and their degree of membership in each of the guidelines of the manual´s of good corporate governance practices of the Brazilian Central Bank. It was elaborated levels of maturity that were joined to a questionnaire to the creation of this tool. These pieces of information were object of the discussion in a meeting with an employee of the Brazilian Central Bank and of the National Confederation of Cooperative Audit, that gave their contributions and declared it is a very useful tool to the cooperativism of credit. This questionnaire was applied in a sample of 46% of the total of the cooperatives that meet the research specifications. It was detected that the cooperatives, on average, adopt 94% of the practices of beginning level, 69% of expanded level, 56% of institutionalized level, 37% of enhanced level and 31% of complete level of maturity in membership to the good corporate governance practices. It was also detected that in the Structure Guideline, the level of maturity is more advanced. In the Inspection Guideline, the beginning practices are totally implanted and the practice of the other levels still have good scope for improvement. On the other hand, the Representativeness Guideline presents the lowest levels of maturity. It can therefore be concluded that the adoption of corporative governance is vital to the cooperatives of credit, being of essential importance that the cooperative manager knows the level of maturity in adherence to good corporate governance practices that its cooperative fits into, because this is the only way to establish goals to its total membership and the consequent reinforcement of his/her cooperative. Therefore, it can be said that the metrics of level of maturity presented in this research is a unique guide to the cooperatives of credit